2016
DOI: 10.1136/archdischild-2015-309777
|View full text |Cite
|
Sign up to set email alerts
|

Tension pneumocephalus induced by high-flow nasal cannula ventilation in a neonate

Abstract: The use of high-flow nasal cannula (HFNC) therapy as respiratory support for preterm infants has increased rapidly worldwide. The evidence available for the use of HFNC is as an alternative to nasal continuous positive airway pressure (CPAP) and in particular to prevent postextubation failure. We report a case of tension pneumocephalus in a preterm infant as a complication during HFNC ventilation. Significant neurological impairment was detected and support was eventually withdrawn. Few cases of pneumocephalus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…In infants weighing <1000 g, we found that flows as low as 4–6 L/min generate average pEEP similar to nCPAP 6 cm H 2 O and flows of 7–8 L/min delivered pEEP higher than nCPAP 6 cm H 2 O. Although rare, HFNC-related complications have been reported 23 24. Awareness of pressures delivered to vulnerable infants is important and may aid clinicians in prescribing flow rates.…”
Section: Discussionmentioning
confidence: 81%
“…In infants weighing <1000 g, we found that flows as low as 4–6 L/min generate average pEEP similar to nCPAP 6 cm H 2 O and flows of 7–8 L/min delivered pEEP higher than nCPAP 6 cm H 2 O. Although rare, HFNC-related complications have been reported 23 24. Awareness of pressures delivered to vulnerable infants is important and may aid clinicians in prescribing flow rates.…”
Section: Discussionmentioning
confidence: 81%
“…The panel judged the anticipated undesirable effects of HFNC compared to COT and NIPPV to be minimal. Adverse events directly related to HFNC are uncommon and have been mostly reported in children and infants [22][23][24][25][26]. The use of HFNC may delay intubation, however the due to the heterogeneity of study designs and risk of confounding we were not able to pool data evaluating this outcome.…”
Section: Rationalementioning
confidence: 99%
“…Recent guidelines urge caution with simultaneous use of high‐flow nasal oxygen and facemask ventilation . Cases of pneumocephalus , pneumo‐orbitus , epistaxis, subcutaneous emphysema, pneumomediastinum, pneumothorax , oesophagealrupture and gastric rupture have all been reported with use of nasal cannulae, largely in paediatrics.…”
Section: Complications Of Apnoeic Oxygenationmentioning
confidence: 99%